Totally laparoscopic gastrectomy using intracorporeally stapler or hand-sewn anastomosis for gastric cancer: a single-center experience of 478 consecutive cases and outcomes - Chen, Ke (World J Surg Oncol, 2016)
BACKGROUND: Totally laparoscopic gastrectomy (TLG) using intracorporeal anastomosis has gradually become mature thanks to the advancements of laparoscopic surgical instruments and the accumulation of operative experience. The goal of this study is to review our institution’s experience with TLG for the treatment of gastric cancer. METHODS: A retrospective study was conducted to examine the short-term outcomes of TLG using intracorporeally stapler or hand-sewn anastomosis performed at Sir Run Run Shaw Hospital between March 2007 and June 2015. The details of intracorporeal anastomosis were described, and the clinicopathological data, surgical outcomes, and postoperative complications were evaluated. RESULTS: Four hundred seventy-eight patients were included in the study. Generally speaking, the patients could be divided into stapler or hand-sewn groups according to whether intracorporeal anastomosis was performed by only hand-sewn technique (n = 97) or only stapling devices (n = 381). For overall patients, the mean operation time and anastomotic time were 225.7 and 30.0 min, respectively. Postoperative complications were observed in 65 patients. All of the patients recovered well without perioperative death by conservative or surgical management. CONCLUSIONS: TLG using intracorporeally stapler or hand-sewn anastomosis is a reasonable option for the treatment of gastric cancer, with early data showing acceptable perioperative outcomes.